PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI PERCETAKAN INDOPRINT KALTIM MANDIRI SAMARINDA - Dina Saputri; Dian Irma Aprianti (University of Widya Gama Mahakam Samarinda, 2021)
This study aims to determine: The Effect of Price, Product Quality and Service Quality on Customer Satisfaction at Indoprint Kaltim Mandiri Samarinda Printing. The sample was taken using the Slovin formula with a total of 97 respondents. The data collection technique uses a questionnaire, the data presented is data obtained from the respondents' answers, using arithmetic tools with the SPSS version 22 program and analyzing the value of multiple linear regression. The results of this study indicate the variable Price (X1), Product Quality (X2), and Service Quality (X3) have a positive effect on Customer Satisfaction (Y), but only the Price variable has a significant result and is the most dominant. The closeness of the relationship between Price, Product Quality and Service Quality to Consumer Satisfaction in choosing the Indoprint Kaltim Mandiri Samarinda printing company is 0.922, with the value from the interpretation table correlation coefficient 0.80 - 1.00. This is able to explain that there is a very strong relationship between Price, Product Quality and Service Quality on Customer Satisfaction in choosing the Indoprint Kaltim Mandiri Samarinda printing company. Price, product quality and service quality affect consumer satisfaction by 85.00%. These results indicate that 85.00% of which affects customer satisfaction by the factors of price, product quality and service quality, while 15.00% is influenced by other factors not examined by this study.